Pre-clinical biomedical research - Denia Morales Navarro (Editorial Ciencias Médicas, 2015)
Introduction: a historical analysis would reveal that the use of animals as test subjects has been both effective and essential. Such a practice has served both to save lives and to answer a variety of biomedical questions. Objective: carry out a bibliographic review about preclinical biomedical research. Methods: abibliographic review was conducted about preclinical biomedical research on the Internet. Most of the papers included in the search have been published in the last five years. An evaluation was performed of international high impact journals from the Web of Sciences dealing with the subject (32 journals), as well as two Cuban journals. Databases from reference systems such as MEDLINE, PubMed and SciELO were consulted with the aid of search terms like " animal research", "preclinical investigation", "biomodels", "laboratory animals", "translational medicine" and their Spanish counterparts. The papers included were in English, Portuguese or Spanish. Of the 136 papers obtained, the reviewers selected the 53 which approached the study subject in a more comprehensive manner. One book was also reviewed. Data analysis and integration: an analysis of the representativeness of papers in the scientific journals where they were published showed that 9.4 % corresponded to the Journal of Clinical Periodontology, and the same percentage to PloS Biology. The remaining papers were evenly distributed among the other journals. Most studies suggest that biomodels are an effective tool in scientific research, but they should be correctly designed, for it is common to find bias in the internal and external validity of the research, leading to errors in scientific publications. Conclusions: lack of knowledge about characteristics inherent to biomodels, preclinical research, methodological design and the very development of the research may lead to errors in the analysis and publication of results, affecting the quality of the research and contributing to the frequent scarcity of reliable animal studies.